Economic Adversity and Voter Turnout: Evidence from Turkish Parliamentary Elections - Kama, Ozge; Aksoy, Tolga; Tastan, Huseyin (SPRINGER, 2022)
This paper investigates the relationship between economic adversity and voter participation in Turkish parliamentary elections. We employ a dynamic model of voter turnout using a cross-regional panel dataset covering all parliamentary elections for the 1987-2018 period. In addition to lagged voter turnout to account for persistency in electoral participation, our models include two measures of economic adversity: inflation, and economic growth. Empirical results indicate that inflation has a positive and significant effect on voter turnout, while economic growth is insignificant in all specifications. Moreover, inflation is associated with higher voter turnout in provinces with a denser population, higher urbanization, and more abundant human capital. Regional voter turnout rates tend to persistently support the habit formation argument. Overall, our empirical results are consistent with the mobilization hypothesis, suggesting that adverse economic conditions lead to higher electoral participation by stimulating voters to punish the government.
Keywords: Voter turnout; Elections; Economic adversity; Turkey; ELECTORAL-PARTICIPATION; INDUSTRIAL DEMOCRACIES; IMPACT; Social Sciences - Other Topics; Sociology